Peran Extended Family dalam Perkembangan Bahasa Anak Usia 7 tahun - Khotijah, Siti; Maghfirah, Febry (UIN Sultan Maulana Hasanudin Banten, 2025)
The research activity was conducted with the aim of knowing the language development of early childhood, especially children aged 7 years who have an extended family background. The case study type is very appropriate to be used in this study, in addition to the data collection method with observation techniques and interviews with Mrs. S, Mrs. Q, and Mrs. J as the biological parents of the three research subjects to obtain information related to children's language development, while the data analysis technique uses the Miles and Hubberman model through several steps of research activities, namely data collection activities, data reduction, data presentation, and drawing conclusions. Based on the results of the observation and interview activities that have been carried out previously, it can be seen that the listening, speaking, writing, reading abilities of Z, A, and R are able to achieve good language development because of the help of stimulation from the family, especially both parents, Grandma, Uncle, and Aunt. Several forms of stimulation, namely through watching videos, singing, telling stories, playing flash cards, and playing kinetic sand are considered effective in stimulating children's language abilities.